2018
DOI: 10.48084/etasr.2143
|View full text |Cite
|
Sign up to set email alerts
|

Delignification of Rice Husk by Microwave Assisted Chemical Pretreatment

Abstract: Rice husk has the potential to be used as a source of alternative energy e.g. as biofuel. Its high lignin content, however, poses difficulty to this use. This study investigates the use of microwave assisted acidic and alkaline pretreatment methods to improve the characteristics of rice husk for energy production. The use of microwave assisted 3.5% NaOH provided optimum pretreatment of rice husk; the lignin content was reduced from 17.8 to 10.2%, the cellulose content increased from 38.6 to 59.3% and the C/N r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Vasconcelos et al studied a sugarcane biomass pretreatment with diluted H 3 PO 4 , and the maximum saccharification was recorded during the pretreatment at 186°C for 8 min [44]. Kaur and Phutela [45], Lag et al [46], and Binod et al [27] also noted an increase in the release of sugars after microwave treatments of paddy straw, coconut husks, and sugarcane, respectively. When deploying thermal hydrolysis, attention should be paid to the possibility of adverse effects, such as the production of phenolic and furan compounds that elicit toxic effects and inhibit the growth of methanogenic bacteria [47].…”
Section: Resultsmentioning
confidence: 99%
“…Vasconcelos et al studied a sugarcane biomass pretreatment with diluted H 3 PO 4 , and the maximum saccharification was recorded during the pretreatment at 186°C for 8 min [44]. Kaur and Phutela [45], Lag et al [46], and Binod et al [27] also noted an increase in the release of sugars after microwave treatments of paddy straw, coconut husks, and sugarcane, respectively. When deploying thermal hydrolysis, attention should be paid to the possibility of adverse effects, such as the production of phenolic and furan compounds that elicit toxic effects and inhibit the growth of methanogenic bacteria [47].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the thermal pre-treatment was carried out by using an autoclave with a temperature of 121 o C and pressure of 15 psi for 2 hours. The same combination of the pre-treatment methods was done by Laghari et al [15] with rice husks that had been ground until 1 mm in size. The optimum conditions for the rice husk pre-treatment were obtained after the thermal pre-treatment using a microwave and continued with the chemical pre-treatment using solution of NaOH 3.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al (2015) delignified mixed hardwood chip powder through conventional hot water bath bleaching using 41% sodium chlorite with a percentage delignification of about 77% albeit addition of five to six charges each hour. Laghari et al (2018) found that on subjecting rice husk to microwaveassisted chemical treatment (with sodium hydroxide, sodium carbonate, hydrogen peroxide and sulfuric acid) the delignification percentage increased by increasing the concentration from 2 to 5%, except for sodium hydroxide where the maximum delignification of about 43% was seen at 3.5% concentration and this being highest of all the treatments. Thus, in the present study, a clear reflection of a synergistic effect on the increase in delignification percentage due to application microwaves and increased concentration of sodium chlorite is seen.…”
Section: Effect On Microwave Power Irradiation Time and Bleaching Solution Concentration On The Delignification Of Rice Strawmentioning
confidence: 97%
“…The results confirmed the disruption of lignin-carbohydrate complex and effective delignification due to application of microwaves. Also, delignification of rice husk by microwave-assisted treatment at 240 watts resulted in almost 30% delignification in just 5 minutes (Laghari et al, 2018). The effect of microwaves is due to the enhanced cell wall rupture and subsequent diffusion caused by unidirectional inside out heat and mass transfers (Veggi et al, 2013).…”
Section: Effect On Microwave Power Irradiation Time and Bleaching Solution Concentration On The Delignification Of Rice Strawmentioning
confidence: 99%